TAJDID PADA AKAD PEMBIAYAAN MURABAHAH DI BANK SYARIAH - Shomad Abd. (Masalah-Masalah Hukum, 2011)
Murabahah principle made by Syariah Banking does not exactly match the definition murabahah known in the scriptures Fiqih. Murabahah which is often described in books Fiqih only involve two parties, namely the seller and buyer. Methods of payment can be made in cash (naqdan) or repayment (bitsaman ajil). Meanwhile, in the Sharia Banking involve three parties. First Aqad made in cash between the bank (as purchaser) and the seller of goods contract is the second installment murabahah made between the bank (as seller) to the bank customers .. Aspects of banking including in Economic Law (Mu'amalah Madaniyah), namely the law that regulates relations in the areas of human wealth, property, and tasharurruf. Applications and modifications in the field muamalah is very possible because basically there is no syariat of absolute and applies to all the time, place. and circumstances (dhuru~. In Islamic Law there is al maqasid ash- syariah which contains the meaning or purpose of things to be ruled. To achieve the purpose, Islamic Syariat indeed itself is dynamic, in a sense can be changed as time requiered. Terms of muamalah, especially on issues related to the banks, is very possible to fit the needs of ijtihad.